The Development of CO2 Capture and Storage Technology in the Field of Architecture and its Challenges and Solutions - Deng, Yuntian (Transactions on Engineering and Technology Research, 2024)
The architecture industry constituted a significant source of carbon emissions, underscoring the urgent need for energy efficiency and emission reduction strategies. In this context, carbon capture and storage (CCS) technologies within the architectural domain emerged as critical research areas. This paper systematically classified and summarized various CCS technologies based on specific sub-fields of architecture, drawing on an extensive review of existing literature. Notably, urban design and planning, building materials, and landscape architecture presented numerous promising carbon sequestration technologies. In urban planning, this paper emphasized the development of supportive planning and decision-making tools aimed at enhancing carbon sequestration efficacy. In the realm of building materials, innovative approaches incorporated CO2 absorption into materials, facilitating permanent carbon sequestration. Meanwhile, landscape architecture focused on refining and optimizing traditional techniques, integrating novel technologies to improve outcomes. The status of these technologies varied considerably, with some having progressed to commercial viability. However, challenges persisted in their widespread adoption. To advance the development of these technologies, this paper highlighted the importance of addressing inherent technical deficiencies and evaluating economic viability, thereby enhancing the dissemination and implementation of carbon sequestration methods within the architecture sector.